KUALITAS PENGAWASAN KEUANGAN DAERAH DI INSPEKTORAT PROPINSI JAWA TENGAH - Setyo Mahanani (Among Makarti, 2018)
AbstractThis study aims to strengthen objectivity, expertise, professional skills and compliance with the code of ethics on the quality of the inspectorate apparatus. A common problem in this studywas the continued increase in state losses caused by corruption and the like. The research sample was taken at the inspectorate of Central Java province. Data were analyzed using Partial Lease Square with SmartPLS 03 software. The results showed objectivity and adherence to the code of ethics of reproduction to the quality of examination, while the expertise and professional skill were not significant on the quality of the examination. The value of things that are jointly shared objectivity, expertise, professional skills and adherence to the code of ethics provide quality to audit quality of 56.4% while the remaining 45.6% by other factor outside the construct. The implication of this research findings for the importance of quality audit is the need for objective attitude of the auditor in addition to the effort to increase the ethical value through coaching and training.Keywords: quality of inspection, objectivity, expertise, professional skills, adherence to the code of ethics.